Pengaruh Model Pembelajaran STEM terhadap Keterampilan Berpikir Kreatif dan Kritis Siswa Sekolah Dasar - Memi Putri Dewita; Amir Luthfi; Nurmalina Nurmalina (Universitas Negeri Makassar, 2023)
The learning model of science, technology, engineering, and mathematics is a learning model that integrates science, technology, methods or techniques, and mathematics in one lesson. This learning model is believed to be used to improve creative and critical thinking skills of primary school students. This study aims to determine how much influence the learning model of science, technology, engineering, and mathematics has on the creative and critical thinking skills of fourth grade primary school students. The method used in this study is a quasi-experimental method. This method has nine stages, namely: literature review, identifying and limiting research problems, developing research hypotheses, making research designs, conducting pretests, conducting experiments, conducting posttests, processing and analyzing data, and drawing conclusions. The research sample was 52 students, consisting of 26 students in the experimental class and 26 students in the control class. The data collection technique used is a test of students' creative and critical thinking skills. The research instrument used was a student's creative and critical thinking skill test sheet. The results of the study can show that the learning model of science, technology, engineering, and mathematics has a significant effect on creative and critical thinking skills of fourth grade primary school students. Therefore, this research can be a reference in applying science, technology, engineering, and mathematics learning models that can improve students' creative and critical thinking skills.